ETHANOL PRODUCTION FROM SUWEG TUBER (Amorphophallus camapanulatus BI.) BY Saccharomyces cerevisiae WITH THE ADDITION OF NPK NUTRITION - Adnyana, Ketut Cahyadi; Kartika, Rudi; Sitorus, Saibun (Jurusan Kimia FMIPA UNMUL, 2020)
Research of ethanol made from suweg tuber flour (Amorphophallus camapanulatus BI.) with the addition of NPK as nutrition Saccharomyces cerevisiae, has been done. The ethanol making process consists of hydrolysis, fermentation, distillation, and testing carried out by Gas Chromatography. The hydrolysis stage is carried out by adding Î±-amylase and glucosyl amylase in order to break the polysaccharide chain into monosaccharide. The fermentation stage is carried out with time variation and NPK concentration. It can be seen that the addition of nutrients of 3.70 g (2%) NPK with a 7 day fermentation time resulted in the most optimum ethanol concentration of 67.357% and an ethanol volume of 7 mL.